PENGARUH SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. HONDA POWER PRODUCT INDONESIA - Faisal Rahman; Resista Vikaliana (Universitas Putera Batam, 2020)
This research was conducted at PT. Honda Power Products Indonesia, with the aim to determine the effect of distribution channels on sales volume at PT. Honda Power Products Indonesia. This research approach is a quantitative approach with correlational research type. Data were collected by distributing questionnaires to 80 samples. From the calculation and data analysis, the linear regression equation is Y = 13.134 + 0.195 X1 + e. The correlation coefficient obtained is 0.694, which means that the Distribution Channel variable has a strong influence on the Sales Volume variable. While the coefficient of determination obtained is 0.489, or 48.9%. This shows that the distribution channel has an influence of 48.9% on volume, while the remaining 51.1% is influenced by other variables not included in the model or not examined by the author. The results of the t hypothesis test show that the Distribution Channel variable has a positive and significant effect on the Sales Volume variable.